Public and private sectors and project solutions Mun River Chi River, Mekong River - Dockthaisong, Professor Dr. Boonton; Songsittikul, Dr.Chamnan; Katphan, Dr.Wasan; Sanwonglakron, Dr.Chatthasanan (The journal of contemporary issues in business and government, 2021)
This research Objective 1) To study problems and obstacles of the public and private sectors and solutions to the Mun Chi River project in Thailand, 2) To study the components of the public and private sectors and solving problems of the Mun Chi River project. Mekong of Thailand and 3) To study management guidelines and recommendations for solving the problems of the Mun River Project, the Chi River, the Mekong River in Thailand is a descriptive study. The Using qualitative research methods Using in-depth interviewing techniques and group chat with important informants the results of the research revealed that the problems and obstacles for the public and private sectors were to review the policies of large-scale water management projects in the Isan region of Thailand as a whole. Find the value that benefits the people Because in the past Development of water management projects, public and private components, and solutions There should be a review of the implementation policy of conventional water management practices aimed at developing large-scale projects in different river basins. Development of various water management projects, management guidelines and suggestions for solutions should focus on the development of large-scale projects in different river basins and public participation in the design of more sustainable alternatives. Not just the government design Because there are still people fishing That take advantage of the tide Not just looking for water